Oral Presentations Abstracts: COVID-19, MEDIA REPORTING, AND THE ROLE OF BIOETHICISTS - NICOLI, Federico; CUMMINS, Paul J.; RAHO, Joseph A. (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 In the aftermath of the 2014 Ebola outbreak, media coverage was scrutinized for sensationalism, weakness in explaining scientific uncertainty, dehumanization of patients, and lack of contextualization. The current COVID-19 crisis presents an opportunity to assess whether the media learned its lesson. Results are mixed. Early reporting on the origin of COVID-19 in “wet markets” indicates that the media continues to do poorly with contextualization. On the other hand, stories on mortality and the infectiousness of COVID-19 indicate there has been improvement. The situation remains fluid as COVID-19 threatens to transform into a pandemic at the time of submission. Data from new countries may alter the reported rates of lethality and infectiousness, and media reporting on these changes may or may not be responsible. The explosion of social media, as a medium to promote reporting, could provide bioethicists a tool to direct the public to reliable stories and criticize inaccurate ones. Using a bioethics perspective, this poster will critically evaluate the quality of U.S. and Italian news media’s reporting on the evolving scientific understanding of COVID-19 and its contextualization. The presentation will employ QR technology to provide links to media coverage of COVID-19 from the U.S. and Italian news media. After critically appraising the quality of COVID-19 reporting, this poster will consider if bioethicists: 1) should provide comment to the media on pandemics; 2) should correct reporting for the public and 3) have a duty to publicly criticize sensationalism in the media.